THE FORMATION OF CONTEMPORARY MULTIFUNCTIONAL SACRED SPACE IN THE CONTEXT OF LITURGICAL AND URBAN TRANSFORMATIONS - Gnatiuk, Liliia (Theory and practice of design, 2025)
The article analyzes the formation of contemporary multifunctional sacred space in the context of European trends in religious architecture. It examines the transformation of liturgical spatial organization principles under the influence of Catholic Church reforms and broader societal changes, and defines the role of the sacred complex as both a social and urban planning nucleus. The aim of the research is to analyze the specific features of liturgical space articulation within the framework of a multifunctional sacred complex. Methodology. The study is based on a comprehensive analysis of contemporary European sacred architecture, a comparative study of architectural solutions for multifunctional complexes, and a critical examination of theoretical works in religious architecture and urban studies. It employs typological analysis, historical and architectural comparison, spatial modeling, and visual environmental analysis. Results. It has been revealed that contemporary multifunctional sacred complexes respond more effectively to the needs of communities, provide openness and integration with the urban environment, and foster the emergence of new social platforms. The articulation of liturgical space aimed at multifunctionality contributes to the dynamism of Christian life and enhances the urban significance of sacred structures. Scientific novelty. The scientific contribution of the study lies in the comprehensive analysis of the influence of contemporary liturgical reforms on the architectural typology of sacred space, and in identifying patterns in the formation of multifunctional sacred complexes as a new model for social and urban development. For the first time, the impact of current liturgical reforms on sacred spatial typologies is examined in a holistic manner, alongside the determination of consistent principles guiding the development of multifunctional sacred ensembles as integral elements of urban and community infrastructure. Practical relevance. The findings of the study may be applied in the design of contemporary religious buildings, the development of urban public spaces, and in the creation of strategies for integrating sacred architecture into the structure of modern cities.